THE EFFECT OF ADVERSITY QUOTIENT, SELF-EFFICIENCY AND SOCIAL FAMILY SUPPORT ON STUDENT ACHIEVEMENT MOTIVATION (CASE STUDY OF DISTANCE LEARNING AT SMAN 67 JAKARTA) - Khoirunnisa; Nurjanah, Siti; Sariwulan, Rd. Tuty (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to analyze the effect of adversity quotient, self-efficacy and family social support on achievement motivation during distance learning at SMAN 67 Jakarta. The method used in this research is descriptive quantitative. The population reached in this study were all 11th grade students at SMAN 67 Jakarta, as many as 287 students. The sampling technique is proportional stratified random sampling. Data was collected using questionnaires or questionnaires distributed via google forms to 143 11th grade students at SMAN 67 Jakarta This study reveals that: 1) adversity quotient has a positive and significant effect of 36.2% on achievement motivation, 2) self-efficacy has a positive and significant effect of 30.3% on achievement motivation, 3) family social support has a positive and significant effect on 23 ,9% on achievement motivation, 4) adversity quotient, self-efficacy and family social support together have a positive and significant effect of 68.4% and the rest are influenced by other factors.